Cognitive performance of breast cancer survivors in daily life: Role of fatigue and depressed mood. Issue 11 (30th August 2019) - Small, Brent J.; Jim, Heather S.L.; Eisel, Sarah L.; Jacobsen, Paul B.; Scott, Stacey B.
Abstract: Objective: Cancer and its treatment are associated with long‐term cognitive deficits. However, most studies of cancer patients have used traditional, office‐based cognitive evaluations instead of assessing patients in their daily lives. Recent research in cognitive aging suggests that variability in performance may be a sensitive indicator of cognitive decline. Using ecological momentary assessment (EMA), we examined cognitive variability among breast cancer survivors and evaluated whether ratings of fatigue and depressed mood were associated with cognition. Methods: Participants were 47 women (M age = 53.3 years) who completed treatment for early stage breast cancer 6 to 36 months previously. Smartphones were preloaded with cognitive tests measuring processing speed, executive functioning, and memory, as well as rating scales for fatigue and depressed mood. Participants were prompted five times per day over a 14‐day period to complete EMA cognitive tasks and fatigue and depressed mood ratings. Results: Cognitive variability was observed across all three EMA cognitive tasks. Processing speed responses were slower at times that women rated themselves as more fatigued than their average ( P < .001). Ratings of depressed mood were not associated with cognition. Conclusions: This study is the first to report cognitive variability in the daily lives of women treated for breast cancer. Performance was worse on a measure of processing speed at times when a woman rated her fatigue as greater than her own average. The ability to identify moments when cognition is most vulnerable may allow for personalized interventions to be applied at times when they are most needed.